2016
DOI: 10.1155/2016/9613908
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Alpha and Medical-Grade Honey Ointments on Cutaneous Wound Healing in Rats

Abstract: Introduction. This study compared the healing efficacy and possible adverse effects of topical Alpha and medical-grade honey ointments on cutaneous wounds in rats. Methods. To conduct the study, 22 male Sprague-Dawley rats were randomly allocated into two equal groups: (1) rats with Alpha ointment applied to the wound surface area and (2) rats with medical-grade honey ointment applied to their wounds. The ointments were applied daily during the 21-day study period. Wound contraction was examined photographical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The characterization of wound lesions indicated by improvements in area of epithelialization, angiogenesis, breaking strength, tissue granulation, collagen deposition, and wound contraction after honey treatment had been performed previously. Some studies reported that the efficiency and efficacy of honey in wound healing was comparable to other usual wound care products such as Intrasite Gel TM [ 71 ], Alpha ® ointment [ 72 ] and hydrocolloid dressing [ 71 ] but more superior than hydrofiber silver and hydrofiber dressings [ 73 ]. The aesthetic outcome of honey treatment was also reported, as thinner scars were formed at wound site of the animals [ 71 ].…”
Section: Honeymentioning
confidence: 99%
“…The characterization of wound lesions indicated by improvements in area of epithelialization, angiogenesis, breaking strength, tissue granulation, collagen deposition, and wound contraction after honey treatment had been performed previously. Some studies reported that the efficiency and efficacy of honey in wound healing was comparable to other usual wound care products such as Intrasite Gel TM [ 71 ], Alpha ® ointment [ 72 ] and hydrocolloid dressing [ 71 ] but more superior than hydrofiber silver and hydrofiber dressings [ 73 ]. The aesthetic outcome of honey treatment was also reported, as thinner scars were formed at wound site of the animals [ 71 ].…”
Section: Honeymentioning
confidence: 99%
“…In this study, five treatment groups were defined for the rat wound healing model: the negative control group, without treatment; Alpha ointment, as a commercial positive control group; basal gel as another positive control group; and 7 and 14 d BSEs (BSE gels) as the two treatment groups. The Alpha ointment is a routine topical medication that is used worldwide for burn wounds [94]. Meanwhile, basal gel was included in order to determine its effect on the wound healing process, as well as to ensure that the effects of the 7 and 14 d BSE gels were not because of their basal gel.…”
Section: Discussionmentioning
confidence: 99%
“…Since treatment is difficult after the formation of burn strictures, the research on treatment must be aimed at preventing stricture formation following the burn. Stricture development occurs with the development of excessive collagen during the healing process and negative wound healing [4].…”
Section: Introductionmentioning
confidence: 99%